2022
DOI: 10.1590/s2175-97902022e201056
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis and in vitro investigation on Citrus flavonoids for inflammatory, diabetic and AGEs targets

Abstract: Flavonoids are a diverse class of polyphenolic substances largely found in plants including citrus peels and are reported to posess a variety of biological activities. We investigated important flavonoids apigenin, hesperidin, narigin, quercetin and tangeritine against diabetes and associated conditions. In current project drug likeness, ADMET analysis, molecular docking and in vitro assays were performed. The apigenin, quercetin and tanagretin exhibited compliance with Lipinski's rule of five. The molecular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The term "oxidative stress" describes the level of oxidation that occurs when the body is exposed to a range of damaging stimuli, causing an imbalance in the body's antioxidant system and tissue damage 15,17,19 . Reactive oxygen species (ROS) generation have been linked in recent years to a number of chronic metabolic disorders, including atherosclerosis and diabetes 14,1622,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "oxidative stress" describes the level of oxidation that occurs when the body is exposed to a range of damaging stimuli, causing an imbalance in the body's antioxidant system and tissue damage 15,17,19 . Reactive oxygen species (ROS) generation have been linked in recent years to a number of chronic metabolic disorders, including atherosclerosis and diabetes 14,1622,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Thiol-containing antioxidant N-acetyl cysteine (NAC), a precursor of glutathione (GSH), protects tissue in vivo by turning it into glutathione (GSH) 13,15,16 . Early studies found that NAC reduced lung injury by preventing neutrophils and vascular endothelial cells from expressing adhesion molecules 7,10,14,15 . Additionally, it entered leukocytes and changed into physiological antioxidants to raise intracellular levels of reduction, causing ROS in cells and media to be inactivated 17,18,23 .…”
Section: Discussionmentioning
confidence: 99%